Fostering Employee Loyalty via Entrepreneurial Behavior: The Mediating Role of the Work Environment - Ali Jufri; Pebi Kurniawan; Sari Laelatul Qodriah; Warda Litvia (Dinasti International Journal of Education Management and Social Science, 2026)
Entrepreneurial behavior plays a crucial role in enhancing organizational sustainability, particularly in small-scale agro-industrial sectors where employee loyalty remains a key challenge. This study aims to examine the effect of entrepreneurial behavior on employee loyalty, with the work environment as a mediating variable in rice milling enterprises. A quantitative approach was employed using a census sampling technique involving 68 employees from three rice mills in Cirebon (PB. AP, PB. Matahari, and PB. NO). Data were collected through structured Likert-scale questionnaires and analyzed using SPSS, including validity and reliability tests, classical assumption testing, multiple linear regression, and the Sobel test for mediation analysis. The results reveal that entrepreneurial behavior has a positive and statistically significant direct effect on employee loyalty, while also significantly influencing the work environment. Furthermore, the work environment positively and significantly affects employee loyalty and partially mediates the relationship between entrepreneurial behavior and employee loyalty, indicating both direct and indirect pathways. These findings highlight the novelty of integrating entrepreneurial behavior and work environment dynamics in explaining employee loyalty. They also emphasize the importance of fostering entrepreneurial practices and supportive work environments to improve employee retention and organizational performance in agro-industrial settings ee retention and organizational performance in agro-industrial settings.